CORRESPONDENCE OF THE PUBLISHING HOUSE OF LATGALE CULTURE CENTRE IN THE 90TIES OF 20TH CENTURY: DISCOURSE OF LANGUAGE - Šuplinska, Ilga (Via Latgalica, 2017)
Considering that at the moment we are working on a broader study about the Latgalian literary trends in modern times (since the 90s of the 20th century), policy determination of the Publishing House of Latgale Culture Centre is an important stage in Latgalian publishing. Originally the Publishing House of Latgale Culture Centre brings together the brightest Latgalian writers, researchers and is the only centre of books published in Latgalian, but at the turn of the century due to various factors the situation changes. In this article correspondence of the Publishing House of Latgale Culture Centre (1990–1997) is used as a source of research from copies of letters which are kept at the research centre of Baltic philology at Rēzekne Academy of Technologies (21 sets of letters with a 191 letters); an interview with the Head of the publishing house Jānis Elksnis and separate articles in periodicals on the activity of the Publishing House of Latgale Culture Centre are sources of this research. The aim of this article is with the help of the mentioned correspondence and available documents to reveal the book publishing policy of the Publishing House of Latgale Culture Centre, its role in Latgalian book publishing, as well as to focus attention on the understanding of the functionality of Latgalian language development in this correspondence and operating policies. Theoretical basis includes ideas of critical discourse analysis represented by Norman Fairclough (1995) and socio-cognitive approach represented by Teun van Dijk (2006), highlighting the role of discursive practices in creating stereotypes and influence of social identity on the creation of specific ideology.Existence of the Publishing House of Latgale Culture Centre all this time, of course, is the merit of the dedication and enthusiasm of the head of the publishing house J. Elksnis. In literary critical terminology, we can say that all the time the Publishing House of Latgale Culture Centre is in a border situation: during the 90s of the 20th century there were a relatively large number of Latgalian writers and scientists, but the publishing, book distribution, marketing skills of the publishing house employees were negligible.This situation was more favourable for Latgalian literature and activity of the Publishing House of Latgale Culture Centre in general during the first decade (1999–2008) of the 21st century: the total number of books published: 241; books published in Latgalian: 81; 5 of them published repeatedly. Throughout the period of existence of this publishing house (according to the available data) 562 books were published, 135 of them in Latgalian or bilingual editions (18 books published repeatedly).Analysis of the correspondence gives a possibility to understand why many problems connected to the Latgalian culture and language are being dealt with so slowly or continue to be unimportant and unknown to wider public.First, assessing the initial stage of activity of the Publishing House of Latgale Culture Centre, it comes obvious that efforts of the non-governmental organizations, dedication and enthusiasm of individual personalities can explain or activate some process, but the solution of the problem or maintenance of a process in long term needs a broader institutional support and focused planning of publishing. On the one hand, the formally defined status of Latgalian “as a historical option of the Latvian language” does not create obstacles for the usage of Latgalian in further and optional education, publishing of books and periodicals and its usage in local municipalities. On the other hand, such status is like a throwback which is remembered about only during pre-election and in discourse on separatism and as a threat to the development of the Latvian literary language and as a tool for entertainment industry to create comical effect or contribute to the development of pop music in another region.Second, the internal disagreement, which emerged in the correspondence between freelancers and volunteers during the 90s, was mainly attributable to the language reform and divided the intellectuals who wrote and read in Latgalian, as a result of which most of elder generation authors protected catholic standards and stood up for the preservation of P. Strods’ writing and V. Locis’ traditions, as well as it was supported by the catholic church in their choice of language to print religious texts, and it was also adopted by the Publishing House of Latgale Culture Centre. Hence the main mission of the Publishing House of Latgale Culture Centre – to cultivate Latgalian language and develop literature – was functioning only in one direction (especially after the adoption of spelling rules in 2008) – maintenance of literary almanac “Olūts” and edition “Tāvu zemes calendars” and creating the background literature, which in fact promoted the so-called third dialect and prevented the young and middle generation from involvement in the development Latgalian cultural environment.